2015
DOI: 10.18632/oncotarget.5032
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cell migration and apoptosis resistance may underlie the association between high SERPINE1 expression and poor outcome in head and neck carcinoma patients

Abstract: High SERPINE1 expression is a common event in head and neck squamous cell carcinoma (HNSCC); however, whether it plays a role in determining clinical outcome remains still unknown. We studied SERPINE1 as a prognostic marker in two HNSCC patient cohorts. In a retrospective study (n = 80), high expression of SERPINE1 was associated with poor progression-free (p = 0.022) and cancer-specific (p = 0.040) survival. In a prospective study (n = 190), high SERPINE1 expression was associated with poor local recurrence-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 60 publications
11
75
0
Order By: Relevance
“…SerpinE1 overexpression also inhibited the activation of caspase‐3 while reducing the number of apoptotic figures at the primary tumor site in vivo. These results are consistent with previous in vitro findings from our group in which serpinE1 overexpression decreased cisplatin‐induced apoptosis by activating PI3K/Akt pathway in HNSCC cells . In agreement with our results, studies conducted in tumor cell lines other than HNSCC reported that serpinE1 can reduce spontaneous and induced apoptosis by blocking Fas/FasL or activating PI3K/Akt survival pathway …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…SerpinE1 overexpression also inhibited the activation of caspase‐3 while reducing the number of apoptotic figures at the primary tumor site in vivo. These results are consistent with previous in vitro findings from our group in which serpinE1 overexpression decreased cisplatin‐induced apoptosis by activating PI3K/Akt pathway in HNSCC cells . In agreement with our results, studies conducted in tumor cell lines other than HNSCC reported that serpinE1 can reduce spontaneous and induced apoptosis by blocking Fas/FasL or activating PI3K/Akt survival pathway …”
Section: Discussionsupporting
confidence: 93%
“…74BserpE1up was obtained by transduction of the 74BGFPLuc HNSCC cell line with the serpinE1‐expressing lentiviral vector (pFUGW_serpinE1) as described previously . 74BGFPLuc and 74BserpE1up cell lines were cultured in Dulbecco's Modified Eagle's Medium (DMEM) containing 10% Fetal Bovine Serum (FBS), 100 U/mL streptomycin/penicillin and 2 mM glutamine (Thermo Fisher Scientific, Waltham, Massachusetts) and maintained in a humidified atmosphere at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study shows that overexpression of THBS2 correlated with poor OS and RFS in CRC patients, which is consistent with our results 21. SERPINE1 expression has been shown to be associated with tumor cell migration and invasion through the activation of the PI3K-Akt pathway 2224. Furthermore, SERPINE1 pro-migratory effect has been associated with LRP1 interaction, which in turn stimulates the Jak/Stat pathway 25.…”
Section: Discussionsupporting
confidence: 91%
“…It reacts directly to integrin, uPA-uPAR and ECM, causing to invade and migrate to surrounding and distance [10, 24]. Meanwhile, SERPINE1 has been considered as biomarker related to poorer prognosis in CRC [11].…”
Section: Discussionmentioning
confidence: 99%